Konstantinopel in den Weltkarten des Beatus von Liébana - Kochanek, Piotr (Vox Patrum, 2011)
Vignettes of Constantinople are on four world maps of the Beatus of Liébana (c. 730- 798): 1) the Beatus map of Saint-Sever (Paris, Bibliothèque Nationale, Ms. Lat. 8878, fol. 45bisv-45terr), 2) the Beatus map of Osma (Burgo de Osma, Archivo de la Catedral, Cod. 1, fol. 34v-35r), 3) the Beatus map of Navarra (Paris, Bibliothèque Nationale, Nouv. acq. lat. 1366, fol. 24v-25r.), and 4) the Beatus map of Arroyo (Paris, Bibliothèque Nationale, Nouv. acq. lat. 2290, fol. 13v-14r). These vignettes are with the period of origin of each map closely connected. In other words, geography, history and political theology are here intimately linked. The vignettes analyzed of the word maps of Beatus illustrate changes in the approach to the question of the role and significance of Constantinople in the eyes of the Latins in the period from 1050 to 1250. These vignettes were certain schemes, that were designed especially for the people of that time and were understood by them. The vignettes were not a universal system, so every mapmaker adorned them with labels in order to avoid ambiguities in the identification of the respective cities. These vignettes were, however, understandable in the context of a specific map, when the map was analyzed against the then geopolitical and theological background. In consequence of this the vignettes of Constantinople on four world maps of the Beatus of Liébana appears as a particular image of the relations between the Latins and the Greeks.